Effects of mobilization treatment on sacroiliac joint dysfunction syndrome - Dogan,Nalan (2021)
SUMMARY OBJECTIVE: This study aims to reveal the short-term effects of exercise therapy and manual therapy plus exercise therapy on pain, quality of life, and physical examination results in the treatment of sacroiliac joint dysfunction syndrome (SIJDS). METHODS: In this study, 64 patients who were participated were divided into two groups. The first group (exercise group) was assigned with the sacroiliac joint (SIJ) home exercise program and the second group (mobilization group) with the combined SIJ manual therapy and home exercise program. Physical examination tests, visual analog scale, and SF-36 evaluation were performed at the beginning of the study, at 24 h, at 1 week, and 1 month after the treatment. RESULTS: Both groups showed that the rate of pain in the posttreatment, after the first week, and the first month; the presence of pain in the sacroiliac region; and VAS values of the patients with SIJDS compared to pretreatment values were clearly decreased (p<0.05). All tests performed in the SIJ physical examination showed significant improvement within both groups (p<0.05). However, there was no statistical difference between the two groups in 1-month period (p>0.05). CONCLUSIONS: We found that the home exercise program and the manual therapy plus exercise program significantly improved pain intensity, quality of life, and the findings of specific tests in patients with SIJDS. In addition, superiority between the two groups in terms of pain intensity, quality of life, and specific tests was not determined.